Language Mapping With Magnetoencephalography: An Update on the Current State of Clinical Research and Practice With Considerations for Clinical Practice Guidelines. Issue 6 (November 2020) - Bowyer, Susan M.; Zillgitt, Andrew; Greenwald, Margaret; Lajiness-O'Neill, Renee
Abstract : Summary: Numerous studies have shown that language processing is not limited to a few brain areas. Visual or auditory stimuli activate corresponding cortical areas, then memory identifies the word or image, Wernicke's and Broca's areas support the processing for either reading/listening or speaking and many areas of the brain are recruited. Determining how a normal person processes language helps clinicians and scientist to understand how brain pathologies such as tumor or stroke can affect changes in language processing. Patients with epilepsy may develop atypical language organization. Over time, the chronic nature of epileptic activity, or changes from a tumor or stroke, can result in a shift of language processing area from the left to the right hemisphere, or re-routing of language pathways from traditional to non-traditional areas within the dominant left hemisphere. It is important to determine where these language areas are prior to brain surgery. MEG evoked responses reflecting cerebral activation of receptive and expressive language processing can be localized using several different techniques: Single equivalent current dipole, current distribution techniques or beamformer techniques. Over the past 20 years there have been at least 25 validated MEG studies that indicate MEG can be used to determine the dominant hemisphere for language processing. The use of MEG neuroimaging techniques is needed to reliably predict altered language networks in patients and to provide identification of language eloquent cortices for localization and lateralization necessary for clinical care.